Epidemiological Study of Eye Diseases and Demographic Factors: A Case Study at Ayu Siwi Eye Clinic Nganjuk in 2024 - Moh Khoirul Anam (Ficco Public Health Journal, 2025)
Background: Vision impairment remains a significant public health concern, particularly among the elderly. This study aims to analyze eye disease trends and patient demographic characteristics at Ayu Siwi Eye Clinic Nganjuk in 2024 to improve prevention and treatment strategies. Methods: This research adopts a descriptive epidemiological approach, utilizing secondary data from patient records. Data on the most common eye diseases and patient distribution based on age, gender, and educational level were analyzed using descriptive statistics, including percentages and frequency distributions. Results: The findings indicate that elderly patients are dominate this study, with 36% in the 40–59 age group and 30% over 60 years old. Female patients (56%) outnumber males (44%), possibly due to longer life expectancy and higher healthcare-seeking behavior. The most prevalent eye disease is immature cataract (31%), followed by primary open-angle glaucoma (7%) and astigmatism (6%). Patients with lower educational backgrounds (30% elementary school graduates) highlight the need for better public eye health education. Conclusions: The study highlight the importance of early screening and preventive measures, particularly for cataracts and glaucoma, to reduce the burden of vision impairment. Expanding access to routine eye examinations and strengthening community-based eye health programs is crucial for at-risk populations.